Real-Time AI-Powered Revenue Assurance Technology Adoption Based on the Theory of Reasoned Action - Tatang Ghogomu, David (Global journal of Business and Integral Security, 2024)
Purpose: Empirical investigation of social influence on adoption of a real-time AI-powered revenue assurance technology (RT-AI-RAT) by retail banks in Cameroon. Methodology: Applied, explanatory, deductive, quantitative and cross-sectional study design. Study instrument psychometric properties tested using Cronbach alpha and exploratory factor analysis. Self-administered questionnaires collected data from participants. Probability-based simple random sampling with a response rate of 14.8% was used. After data screening and regression assumption verifications, GNU PSPP (Release 1.6.2-g78a33a) software employed linear regression for data analysis. Main Results: The hypothesis was supported in significance (p= 0.05) but not directionally (B= -27). Social influence explained 20% of the effects. Conclusions: Social influence had a significant negative effect on Cameroon retail banks’ intention to use RT-AI-RAT hence continuing CAATs use. High unawareness of the technology and mal-practice were speculated causes. Paper Type: Research paper Keywords: Real-time, Artificial Intelligence (AI), Automation, Audit, Banks, Revenue Assurance, Theory of reasoned action (TRA), Cameroon.